One-Step Biosynthesis of Vitamin C in Saccharomyces cerevisiae - Zhou, Mengyu; Bi, Yanhui; Ding, Mingzhu; Yuan, Yingjin (Frontiers in Microbiology, 2021)
Vitamin C (VC) is comprehensively applied in foods, cosmetics, pharmaceuticals and especially clinical medicine. Nowadays, the industrial production of VC mainly relies on the classic two-step fermentation route, and researchers have explored the way for one-step fermentation of VC in recent years. In this study, a VC biosynthesis pathway that directly produced VC from glucose was reconstructed in Saccharomyces cerevisiae, and the protein engineering and metabolic engineering strategies was adopted to improve it. Firstly, five exogenous modules from Arabidopsis optimized by synthetic biology approaches were introduced into the chassis cells to obtained Strain YLAA harboring VC biosynthesis. In addition, L-galactose dehydrogenase (L-GalDH) and L-galactono-1,4-lactone dehydrogenase (L-GLDH) were fused and expressed in S. cerevisiae cells for the first time, which increased the intracellular VC accumulation by 2.78 folds, reaching 9.97±0.09 mg/L. Through copy number engineering, it was further confirmed that the last step catalyzed by L-GLDH is the rate-limiting step. GDP-L-galactose phosphorylase (GPP) encoded by vtc2 is another rate-limiting enzyme confirmed by GAL1p overexpression results. Finally, by balancing gene expression and cell growth, the highest production strain with overexpressing vtc2 by multicopy plasmids was constructed. The VC accumulation reached 24.94±1.16 mg/L, which was currently the highest production from glucose in S. cerevisiae. The production of the recombinant strain reached nearly 44 mg/L with the exogenous addition of L-galactose or glutathione. The results further emphasized the importance of the step catalyzed by GPP. The investigation provided experience for the efficient biosynthesis of VC and the determination of rate-limiting steps.